Movement analysis systems and their application to study karate techniques - Witte, K.; Edelmann-Nusser, J.; Campe, S. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction Until now there are only few biomechanical researches of karate techniques. One reason is that kinematic analyses of rapid movements make high demands on technical equipment(e.g. Sforza et al., 2000). The focus of this presentation are three motion analysis systems, which are tested with regard to their applicability to analyse karate techniques: AS200 on infrared basis, Zebris on ultrasound basis and SIMI0Motion on digital video basis. These systems are compared with each other for two karate techniques with respect to their spatial and temporal resolutions. Methods The special characteristic of karate techniques is their velocity-time relationship: Generally first there is an acceleration up to a high velocity followed by a high active deceleration so that there in no impact that could injure the opponent. As well, a high precision of the movement is necessary. Therefore high spatial and temporal resolutions of the motion analysis systems are required. The estimation of the spatial-temporal resolutions was done under three different conditions: Positions, velocities and accelerations of fixed objects, of objects with constant velocity and of free falling objects were computed using AS200 at 600Hz (max. scan rate of the system), Zebris at 100Hz (max. scan rate of the system) and SIMI0Motion with a JVC GR-DVL 9800 camera at 200 Hz. As karate techniques the combination of Age-Uke and Gyaku-Zuki were analysed Results It can be concluded that the AS 200 and the SIMI0Motion-system provided the best results for all three conditions. The AS200 showed the best spatial and, because of the scan rate, the best temporal resolution of the three systems and therefore we got the best results with this system computing accelerations. For the Zebris system neither the spatial nor the temporal resolution were suitable. Fig. shows the velocity-time course of the left and right wrists in karate acquired with the SIMI0Motion system. From this diagram it is possible to determinate the peaks of the velocities and the time delay between both movements. In our opinion, these curves help to characterize the above-mentioned karate techniques. Discussion/Conclusion Because the scan rate of the AS200 is three times higher than the scan rate of the SIMI0Motion combined with a JVC GR-DVL 9800 camera, the temporal resolution of the AS200 is better. This could be corrected in SIMI0Motion using cameras with higher frame rate. But, the advantage of the AS200 is the quick analysis: For the markers are active markers and transmit a digital identifier, they are detected automatically without any failings even if a marker is temporarily hidden. The automatic detection in SIMI0Motion is more problematically and therefore we often had to do a manual analysis. However, we have to note that only the SIMI0Motion realizes the simultaneous observation of the biomechanical characteristics and the video. Hence for the analysis of a large number of trails at a high scan rate as necessary for technique analyses of rapid movements like in karate, the AS 200 is more comfortable and practicable.